The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1980-4415v30n55a17
|View full text |Cite
|
Sign up to set email alerts
|

Manifestaciones de los Profesores de Matemáticas sobre sus Prácticas de Evaluación de la Resolución de Problemas

Abstract: ResumenLa evaluación es uno de los organizadores del currículo que debe formar parte del proceso de enseñanza y aprendizaje, además a través de ella se constata la adquisición de aprendizajes. Conjuntamente, entendemos que resolver problemas es un objetivo de aprendizaje, tal y como se refleja en las propuestas curriculares, por lo que éste se convierte en objeto de evaluación. En nuestra investigación elaboramos un cuestionario sobre la evaluación de la resolución de problemas a partir de las demandas que se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…In most of these episodes, where the assessors compare their responses with the assessed ones, future teachers were trying to understand the mathematical expression that their peer gave as solution (case 1) or valuing the fact that their peer presented only particular solutions to the problem (case 2). These results show the influence of the attachment to one's own solution in the peer assessment processes, already mentioned in other studies (e.g., Cárdenas et al, 2016).…”
Section: / 17supporting
confidence: 86%
See 3 more Smart Citations
“…In most of these episodes, where the assessors compare their responses with the assessed ones, future teachers were trying to understand the mathematical expression that their peer gave as solution (case 1) or valuing the fact that their peer presented only particular solutions to the problem (case 2). These results show the influence of the attachment to one's own solution in the peer assessment processes, already mentioned in other studies (e.g., Cárdenas et al, 2016).…”
Section: / 17supporting
confidence: 86%
“…This type of evaluation focuses exclusively on the final result. However, not specific aspects of problem-solving are assessed, such as the search of strategies, the existence of multiple solutions or reflection on the solution obtained and the strategy used (Felmer & Perdomo-Díaz, 2016), although they are aspects that teachers consider important to assess (Cárdenas et al, 2016). Arnal-Bailera et al (2018) found that mathematics university teachers notice five main aspects when assessing problemsolving tasks: We analyze if future secondary mathematics teachers notice those problem-solving characteristics and if there are other attributes that they look at.…”
Section: Problem-solving and Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…En nuestro estudio nos centraremos en la evaluación a partir de la calificación en una prueba (Castillo y Cabrerizo, 2003) puesto que, al evaluar la prueba de matemáticas de las PAU, lo que estamos haciendo es valorar el aprendizaje de cada alumno y en qué grado ha alcanzado los conocimientos, destrezas o habilidades matemáticas que se miden en esta prueba a partir de las evidencias que quedan sobre el papel. Pese a la diversidad de enfoques y de instrumentos existentes para la evaluación y pese a que calificar exámenes de respuesta abierta es un proceso complejo (Wang y Cai, 2018), lo cierto es que, en la práctica, es muy común el uso de este tipo de pruebas para la evaluación de los alumnos (Cárdenas, Blanco, Guerrero y Caballero, 2016;Moro-Egido, 2016). La evaluación tiende así a identificarse con la calificación de dichas pruebas (Senk, Beckmann y Thompson, 1997).…”
Section: Evaluación En Pruebas Escritasunclassified